Maximal and submaximal oxygen uptake during running: how should body mass be accounted for? - Svedenhag, J. (Scandinavian Journal of Medicine & Science in Sports, 1995)
Oxygen uptake during running, i.e., the running economy, is an important factor in determining running performance in endurance events. The relation to performance is particularly strong when the aerobic running capacity is calculated, i.e., when running economy is related to the maximal oxygen uptake. There is considerable interindividual variation in running economy, and the reason for this is only partly understood. To some extent, this may be due to the way in which the oxygen uptake during running is usually expressed. This may especially be true when subjects with different or changing body masses are compared. Several lines of evidence, including earlier animal studies as well as more recent human studies, favor the expression of submaximal and maximal oxygen uptake during running in terms of ml.kg-0.75.min-1 rather than as ml.kg-1.min-1.